Formulasi dan Stabilitas Mutu Fisik Sediaan Lulur Serbuk dari Ampas Kopi Arabika (Coffea arabica) Gayo, Ubi Jalar Ungu (Ipomea batatas L) dan Rimpang Jahe (Zingiber officinale) - Elfariyanti, Elfariyanti; Zarwinda, Irma; Zakaria, Nurmalia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Scrub is a traditional cosmetic preparation that has been prescribed for generations and is used to remove dead skin cells, dirt, and open pores so that air exchange is free and the skin becomes brighter and whiter. Previous research reported that Gayo Arabica coffee grounds discarded as waste contain antibacterial and antioxidant compounds. Purple sweet potatoes are reported to contain natural antioxidants because they contain anthocyanins and beta-carotene, apart from that, ginger rhizomes are reported to be able to inhibit the growth of bacteria that cause body odor on human skin. Therefore, these three ingredients have the potential to be used as ingredients for making natural powder scrubs. This research aimed to determine the effect of the proportion of Gayo Arabica coffee grounds, purple sweet potato, and ginger rhizome on the finished product of powdered scrub preparations as seen from the stability of their physical quality. The research method used was experimental in the laboratory with a Completely Randomized Design (CRD). The powder scrub formulation is made in 3 formulas (F1, F2, and F3) by varying the ratio of the amount of Gayo Arabica coffee grounds, purple sweet potato, and ginger rhizome respectively, namely F1 (1:3:1), F2 (2:2: 1) and F3 (3:1:1). The weight of each formula is 100 g. The physical quality stability test of the powder scrub preparation was carried out on the 1st, 7th, and 14th days including organoleptics, water content, homogeneity, pH, drying time, and adhesion. The test results showed that during 2 weeks of storage, the body scrub preparations that were made had met the requirements for good physical quality. In the organoleptic test, the color, shape, and odor of the preparation did not change, the preparation was homogeneous, the pH was stable at 6.2, and the water content was stable at below 10% where the F3 formula showed the lowest water content. The results of the drying time test meet the requirements, namely a minimum of 15 minutes and the adhesion test meets the requirements, namely greater than 1 second.